2022
DOI: 10.17219/dmp/145287
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the application of software on the volumetric and cross-sectional assessment of the oropharyngeal airway of patients with and without an open bite: A CBCT study

Abstract: Background. Using different software to evaluate the airways, with different thresholds, but within the range for airway recognition, could yield different measurements in the same patient with or without craniofacial disharmony. Objectives.The aim of the present study was to compare the volume and the most constricted area (MCA) of the oropharynx in individuals with or without an open bite by using 2 software programs meant for cone-beam computed tomography (CBCT).Material and methods. This comparative study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
(66 reference statements)
0
5
0
Order By: Relevance
“…Our patient suffered from narrow airways, which might be typological for several types of malocculsions. Our patient suffers from a class II deep bite, which is also one of the factors that could cause narrowing of the airways [ 10 , 11 ]. As shown in other research [ 11 ], class II corrections result in a widening of the airways.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient suffered from narrow airways, which might be typological for several types of malocculsions. Our patient suffers from a class II deep bite, which is also one of the factors that could cause narrowing of the airways [ 10 , 11 ]. As shown in other research [ 11 ], class II corrections result in a widening of the airways.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between malocclusion and breathing patterns is an interrelated phenomenon. Malocclusion can contribute to improper breathing patterns, and conversely, improper breathing patterns can exacerbate malocclusion [ 20 ]. Our study’s findings provide critical insights into the latter aspect, showing how nasal breathing may positively influence CBMD and MCW at specific mandibular points in different age groups.…”
Section: Discussionmentioning
confidence: 99%
“…It was also demonstrated that orthodontic diagnosis can be changed [4][5][6]. Another study performed on two groups of 60 cases selected from 137 CBCT scans obtained from patients with and without an open bite (each group including adults of both genders and approximately equal mean age) demonstrated how two different three-dimensional software packages (Planmeca Romexis and Nemotec NemoStudio) used in CBCT interpretation affect the volumetric and cross-sectional measurements of the oropharyngeal airway, particularly in individuals without an open bite [7]. In addition, recent research indicates the correlation between skeletal Class II malocclusion and the position of the mandibular condyle affecting the temporomandibular joint (TMJ) and breathing.…”
Section: Introductionmentioning
confidence: 99%